Deconstructing the relationships between self‐esteem and paranoia in early psychosis: an experience sampling study - Monsonet, Manel (Br J Clin Psychol, 2020)
BACKGROUND: No studies have examined the association between self‐esteem and paranoia developmentally across the critical stages of psychosis emergence. The present study fills this gap and extends previous research by examining how different dimensions, measures, and types of self‐esteem relate to daily‐life paranoia across at‐risk mental states for psychosis (ARMS) and first episode of psychosis (FEP) stages. Furthermore, the moderation effects of momentary anxiety and momentary perceived social support on the association between momentary self‐esteem and paranoia were examined. DESIGN: This study used a multilevel, cross‐sectional design. METHODS: One‐hundred and thirteen participants (74 ARMS and 39 FEP) were assessed repeatedly over seven consecutive days on levels of momentary paranoia, self‐esteem, anxiety and perceived social support using experience sampling methodology. Measures of trait and implicit self‐esteem were also collected. RESULTS: Global momentary and trait self‐esteem, and their positive and negative dimensions, were related to daily‐life paranoia in both ARMS and FEP groups. Conversely, implicit self‐esteem was not associated with daily‐life paranoia in either group. Anxiety negatively moderated the association between positive self‐esteem and lower paranoia, whereas both feeling close to others and feeling cared for by others strengthened this association. However, only feeling cared for by others moderated the association between negative self‐esteem and higher paranoia. CONCLUSIONS: Different types, measures and dimensions of self‐esteem are differentially related to paranoia in early psychosis and are influenced by contextual factors in daily‐life. This yields a more complex picture of these associations and offers insights that might aid psychological interventions. PRACTITIONER POINTS: Different measures (trait and momentary) and dimensions (positive and negative) of explicit self‐esteem are distinctly related to paranoia across risk and first‐episode stages of psychosis. Explicit, but not implicit, self‐esteem is associated with real‐life paranoia in incipient psychosis. Anxiety boosted the association of poor self‐esteem and paranoia ideation in daily‐life. Social closeness, but feeling cared for by others in particular, interacts with self‐esteem tempering the expression of paranoia in real life.